The association between patent foramen ovale and unexplained syncope in pediatric patients - Runmei Zou; Shuo Wang; Ping Liu; Donghai Chen; Jun Yan; Hong Cai; Yuwen Wang; Cheng Wang (BMC, 2024)
Abstract Background Patent foramen ovale (PFO) is associated with transient ischemia attack (TIA) or stroke, paradoxical embolism, and migraines. PFO closure decreases the recurrent incidence of cerebral ischemic events and reduces the incidence of syncope in adults. However, whether PFO is associated with syncope in pediatric patients has not been investigated. Methods 1001 pediatric patients (aged 4 to 17 years, mean age 10.31 ± 2.61 years, 519 males) who complained of unexplained syncope, palpitation, headache, dizziness and chest pain and were hospitalized in the Syncope Ward, The Second Xiangya Hospital, Central South University between January 2013 and April 2022 were recruited. Children with definite etiology of syncope, neurological, cardiogenic, psychological and other system diseases were excluded. PFO was measured by transthoracic echocardiography and right-heart contrast echocardiography was performed to identify the presence of right-to-left shunting. The demographic data and medical records were retrospectively reviewed and analyzed. Results 276 cases were included in the simple syncope group, 379 cases in the headache/dizziness group, 265 cases in the chest pain group, and 81 cases in the palpitation group. The incidence of PFO between the four groups was insignificant (4.71%, 4.74%, 4.15%, 6.17%, respectively, P = 0.903). Multivariate Logistic regression demonstrated that PFO is not associated with the increased risk of syncope (P = 0.081). Conclusion PFO may not increase the risk of syncope in pediatric patients. Further study may include a large and multicenter sample to investigate the association between PFO and unexplained syncope.